Bibliotherapy. Reading Recomendation experiencing Exclusion during COVID-19 - Janavičienė, Daiva (Slauga. Mokslas ir praktika, 2021)
The relevance of the research is based on more than a year-long restrictions experienced by people of Lithuania and worldwide because of the COVID-19 pandemic. The theoretical part presents a concept for bibliotherapic recommendations for reading. From an interdisciplinary point of view, the research integrates insights from the domains of psychology, public health, information and communication and literary criticism. Individuals experiencing psychological problems, by delving into literature which encourages reflection of humanistic values, during their in-depth reading process, can not only distract themselves from stressful everyday life but also, while identifying themselves with personages of literary works, better conceive themselves and their environment as well as find new ways to solve their problems. This justifies the applicability of bibliotherapy for those who experience social exclusion during the pandemic.The open survey collected data from 17 experts (12 members of the Lithuanian Bibliotherapy Association and 5 practitioners involved in bibliotherapy projects; 4 study participants from the health service sector (psychotherapists); 6 representatives from the education sector; and 7, from the cultural sector). A recommendatory list of books for passive bibliotherapy sessions was drawn. The list comprises 2 topics: (1) recommendations for general bibliotherapy and (2) fiction for health practitioners (81 books in total, 43% of which are accessible online). Every entry in the list includes metadata required for the identification of the work (AUTHOR and title), a brief substantiation of bibliotherapic aspects formulated by experts and the information about the accessibility of the book on the portal ibiblioteka.lt. The list of bibliotherapic literature can be also useful for health practitioners, social activities professionals, organisers of local community activities, librarians and those who wish to provide help by reading.
Keywords: helping by reading; deep reading; psychological self-help